GROWTH AND SURVIVAL OF TILAPIA (Oreochromis niloticus) WITH STARVED PERIODICALLY IN BEDENG MUNIR VILLAGE, SOUTH PAGAR ALAM - Verma Agustina; Retno Cahya Mukti (AQUASAINS, 2022)
Abstract This time fish farmers often face constraints on the high price of commercial feed which results in low profits for the farmers. One solution to reduce artificial feed is periodic starvation. Starvation can reduce and increase feed efficiency while increasing production and fish can grow equally without fasting. The purpose of this study was to determine the growth and survival of periodically fasted tilapia (Oreochromis niloticus) in Bedeng Munir Village, South Pagar Alam. The method used in fish farming consisted of two treatments, that is P0: control and P1: fasting treatment (fish were given commercial feed for 4 days and fasted for 1 day). The parameters observed were absolute length growth, absolute weight growth, total feed consumption, feed efficiency, survival, and water quality. The results showed that the P1 treatment produced the highest absolute weight growth of 16.5 g, the highest absolute length growth was 1.35 cm, the lowest amount of feed consumption was 1540 g, the highest feed efficiency was 204.94%, the survival rate was 89. %,. While water quality in both the treatment is still in the range of tolerance for tilapia as temperature 21.4 to 24.2 0C and pH 7.6 to 8.1.KeywordsGrowth, tilapia, starvation, survival.